Welding for beginners : learn everything you need to know to weld, cut, and shape metal - Christena, Stephen Blake (New Shoe Press, an imprint of The Quarto Group, 2022)
Learn to weld, step by step, with this beginner's guide. Welding for Beginners, adapted from Stephen Blake Christena's Learn to Weld, has culled the absolute basics that are required to build a successful welding hobby and illustrated them in these pages. Both practical and inspiring, this book teaches you the basic equipment you will need, setting up your work area, techniques for beginners with project ideas for practicing your skills, dos and don'ts, and welding safety. If you are inexperienced and want to start out strong-whether working in a home workshop, school workshop, blacksmith shop, or auto shop-this is the perfect reference. The projects illustrate the basic foundation techniques that every welder needs to know, while also helping you tackle problems and fix mistakes as well as shortcuts and level ups. Photographs and illustrations teach welding and clear, concise, easy-to-read text takes all the confusion out of the learning the processes. This easy-to-use book includes: Welding techniques for simple practical repairs and small artisan home projects Safety and protective gear Workshop set-up plans Basic equipment and upkeep Basic welding types, including arc and MIG Common mistakes and troubleshooting Project ideas Instructive photos showing process details for successful results Tons of quick tips and welding hacks to give beginners a strong foundation to improve upon Get welding!